Training loads and RSA and aerobic performance changes during the preseason in youth soccer squads - Cetolin T. (2018)
© 2018 Editorial Committee of Journal of Human Kinetics.The aims of this study were to compare the internal training load (ITL) in soccer players of two competitive age groups (under-15 [U-15] and under-19 [U-19]) during an 8-week preseason training period and compare the associated changes in physical performance measures. Eighteen U-15 and twelve U-19 players were monitored over an 8-week period during the preseason phase. The ITL was monitored using the session rating of perceived exertion (RPE) method. Before and after the preseason period, physical performance was assessed by best (RSAbest) and mean (RSAmean) times in a repeated sprint ability (RSA) test and peak velocity derived from the Carminatti test (PVT-CAR). Total weekly ITL increased with age (U-15: 13770 ± 874 AU vs. U-19: 33584 ± 2506 AU; p < 0.001). In addition, U-19 players perceived training sessions as heavier than U-15 players (6.1 ± 0.3 vs. 5.3 ± 0.3 AU, respectively; p < 0.001). After the preseason period, very likely to almost certainly positive changes were observed for all performance measures in both age groups. However, the U-15 group had possibly superior gains in RSAbest (+1.40%, 90%CL -0.29 to 3.05, with ES = 0.35) and likely higher effects in RSAmean (+1.89%, 90%CL 0.04 to 3.70, with ES = 0.53) and PVT-CAR (+2.71%, 90%CL 0.35 to 5.01, with ES = 0.37) compared to the U-19 group. In conclusion, our findings demonstrate that the U-19 group accumulate higher total weekly ITLs than the U-15 group during the preseason phase due to longer and heavier training sessions. However, the U-15 group obtained superior gains in soccer-specific physical abilities while accumulating half the total ITLs during lighter training sessions.